Ibuprofen, a household pharmaceutical belonging to the racemic mimic class-chirality, diastereochemical details, packing and overlay of the pair within the (S)(+) crystals - Bernal, Ivan; Lalancette, Roger (European Journal of Chemistry, 2025)
We have discovered that enantiopure and racemic Ibuprofen crystallize with nearly the same cell constants, the former in space group P21, the latter in P21/c. As expected from a pair that belongs to the racemic mimic class, the values of Z’ are 2.0 and 1.0, respectively. Interestingly, despite the fact that one is enantiopure and the other is a racemate, they form the classical dicarboxylate dimer one is familiar with in elemental chemistry and with nearly identical geometrical parameters, the enantiopure sitting at a true lattice inversion center, and the other one at a pseudo-inversion point located at 0.5000, 0.4458, and 0.5000. Packing diagrams are provided that show the remarkable degree to which they agree. Overlay diagrams generated with Mercury illustrate the extent to which the pair of enantiopure species resemble each other; the differences being largely small diastereoisomeric discrepancies and without a doubt the result of anisotropy in packing forces. Finally, within accepted limits for π-π bondings, there are no significant interactions between the phenyl rings in either crystalline form.